The effect of corporate governance quality on the strategic use of Non-GAAP disclosures to beat earnings benchmarks - Nunes, Filipa dos Reis (2013)
This study investigates the impact of corporate governance quality on the use of non-GAAP earnings measures to beat strategic earnings benchmarks. For this purpose, five strategic earnings benchmarks are considered: beating analysts’ forecasts, reporting growth in profits, portraying better performance, beating industry performance and avoiding losses. Firms’ governance quality is measured through an index combining 41 attributes. For a sample of European firms, empirical results suggest that corporate governance has a strong influence on firms’ voluntary disclosure decisions. Overall, firms’ governance quality is capable of reducing managers’ propensity to use non-GAAP metrics to meet or beat earnings thresholds. However, it does not seem to have similar influence on all benchmark beating strategies. In fact, the discretionary disclosure of non-GAAP earnings to exceed analysts’ forecasts and to avoid losses is not mitigated by good governance practices. Also, governance mechanisms reduce the magnitude of the difference between non-GAAP earnings and both GAAP measures and analysts’ expectations.